2018
DOI: 10.1021/acs.energyfuels.7b02962
|View full text |Cite
|
Sign up to set email alerts
|

Structure and SO2 Absorption Properties of Guanidinium-Based Dicarboxylic Acid Ionic Liquids

Abstract: A new series of functionalized ionic liquids (ILs) with 1,1,3,3-tetramethylguanidine ([TMG]+) cations as well as dicarboxylic acid anions {[−OOC–(CH2–CH2) n –COO–], where n = 1, 3, and 5} was synthesized, and their SO2 absorption properties were investigated. A high SO2 absorption capacity of the prepared ILs was achieved. The molar ratios of SO2 to [TMG]­[succinic acid] {([TMG]­[SUC]) (n = 1)}, [TMG]­[suberic acid] {([TMG]­[SUB]) (n = 3)}, and [TMG]­[dodecanedioic acid] {([TMG]­[DOD]) (n = 5)} were 4.76, 5.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…The syntheses of ILs in this experiment follow methods reported in literature. For example, [TMG]­[Lac] was prepared by mixing 1,1,3,3-tetramethylguanidine and lactic acid in a 1:1 molar ratio in an ice-water bath, after which the mixture was stirred for 5 h. The water in the synthesized ILs was removed using rotary evaporators, followed by N 2 bubbling at 80 °C for 24 h. The methods for synthesizing 1,1,3,3-tetramethylguanidinium suberate ([TMG]­[SUB]), 1,1,3,3-tetramethylguanidinium dodecanedioate ([TMG]­[DOD]), and [TMG]­[BF 4 ] were the same as those reported in the literature. Karl-Fischer moisture titration was used to determine the moisture contents of functional ILs. The moisture contents of the synthesized ILs were less than 3%.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The syntheses of ILs in this experiment follow methods reported in literature. For example, [TMG]­[Lac] was prepared by mixing 1,1,3,3-tetramethylguanidine and lactic acid in a 1:1 molar ratio in an ice-water bath, after which the mixture was stirred for 5 h. The water in the synthesized ILs was removed using rotary evaporators, followed by N 2 bubbling at 80 °C for 24 h. The methods for synthesizing 1,1,3,3-tetramethylguanidinium suberate ([TMG]­[SUB]), 1,1,3,3-tetramethylguanidinium dodecanedioate ([TMG]­[DOD]), and [TMG]­[BF 4 ] were the same as those reported in the literature. Karl-Fischer moisture titration was used to determine the moisture contents of functional ILs. The moisture contents of the synthesized ILs were less than 3%.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…For example, Alcantara et al (2018) (Reddy et al, 2015;Porwal et al, 2016;Singh et al, 2017). In recent years, TMG-based PILs were applied in acid gases absorption due to low viscosity, simple synthetic routes and excellent absorption performance (Jin et al, 2011;Meng et al, 2018 (Jessop et al, 2012). Recently, a novel method for CO 2 capture by tunable anionfunctionalized PILs based on the single-site interaction between the CO 2 and electronegative nitrogen or oxygen atom was reported, it was shown that CO 2 absorption capacity can be easily tuned by the IL basicity (Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[DOD] (Scheme 4), and their corresponding SO 2 solubility is 3.0, 8.74, 5.96, 4.76, and 5.96 mol of SO 2 per mol of ILs at 25 °C, respectively. 44,45 Anions of the ILs, as the main factor, greatly influence the solubility of SO 2 . In these , the increased chain length in the anion enlarges the asymmetry of ILs and decreases the space resistance, avoiding SO 2 crowding in the interstice and causing the hydrogen atom of methylene to interact with SO 2 easily.…”
Section: [Glycerol] [Tmg][pbe] [Tmg][sub] [Tmg][suc] and [Tmg]mentioning
confidence: 99%